Metode Geographically Weighted Panel Regression (GWPR) Untuk Menganalisis Faktor Yang Mempengaruhi Kemiskinan Di Provinsi Sumatera Utara - Andrew Lupe Tiopan Sitorus; Elmanani Simamora (Dinasti Research, 2023)
This study aims to analyze the factors of population density, life expectancy, years of schooling, open unemployment rate, per capita monthly food expenditure, population with health complaints, economic growth, human development index, households with access to proper drinking water and households with access to proper sanitation on the percentage of poverty in North Sumatra province. This research is based on secondary data available at the North Sumatra Central Bureau of Statistics in 2017-2021. The factor analysis used in this study is Geographically Weighted Panel Regression (GWPR) which is a combination of the Geographically Weighted Regression (GWR) method with the panel data regression method. The results of the research analysis show that simultaneously the factors of population density, life expectancy, open unemployment rate, monthly per capita food expenditure, population with health complaints, households with access to proper drinking water have no significant effect. If tested simultaneously, only the factor of households having access to proper sanitation has a significant effect on the percentage of poverty. However, partially, these factors have a significant effect on the percentage of poverty.